Die Familie Mendelssohn 1729-1847 I. Teil - Hensel, Sebastian 1830-1898 ([Berlin] [Behr], 1880)
Sebastian Hensel, a great-grandson of the philosopher Moses Mendelssohn and son of Fanny Mendelssohn, wrote this family chronicle in 1879. The Mendelssohn family is a German-Jewish family of scholars, bankers and artists. For many years, the descendants remained connected through the joint management of the Mendelssohn banking house. Numerous artists also descended from the family - among them the famous composer, pianist and organist Felix Mendelssohn Bartholdy.
Title page is missing
See 10G11 for the complete first edition and 08B26 for the second part in the third edition
Originally published in 1879 (see 10G11)
Keywords: Mendelssohn family; Jews; 18th Century (1701-1800); 19th Century (1801-1900); Composer; Biography; Germany